Role of Dietary Factors, Food Habits, and Lifestyle in Childhood Obesity Development: A Position Paper From the European Society for Paediatric Gastroenterology, Hepatology and Nutrition Committee on Nutrition. Issue 5 (22nd May 2021) - Verduci, Elvira; Bronsky, Jiri; Embleton, Nicholas; Gerasimidis, Konstantinos; Indrio, Flavia; Köglmeier, Jutta; de Koning, Barbara; Lapillonne, Alexandre; Moltu, Sissel Jennifer; Norsa, Lorenzo; Domellöf, Magnus
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Childhood obesity has high societal and economic impact but current treatment approaches are sub-optimal. In the last decade, important studies have been conducted aiming to identify strategies to prevent obesity during critical periods of life. Updated recommendations for childhood obesity prevention are needed. We present data from systematic reviews and meta- analysis, randomised controlled trials (RCTs) and large observational studies, published from 2011 onwards that consider the possible role of the following factors in obesity development: breast-feeding; macronutrient composition and method of complementary feeding; parenting style; dietary patterns; sugar-sweetened beverage consumption; eating behaviour (eg, skipping breakfast, family dinners. etc); meal frequency and composition (fast foods, snacking), portion size; dietary modulators of gut microbiota (including pre-, pro-, and synbiotics); physical activity and sedentary behaviour. We used the Medline database and the Cochrane Library to search for relevant publications. Important research gaps were also identified. This position paper provides recommendations on dietary factors, food habits, and lifestyle to prevent childhood obesity development, based on the available literature and expert opinion. Clinical research and high-quality trials are urgently needed to resolve numerous areas of uncertainty.